Allodepleted T‐cell immunotherapy after haploidentical haematopoietic stem cell transplantation without severe acute graft‐versus‐host disease (GVHD) in the absence of GVHD prophylaxis. (28th May 2019) - Roy, Denis Claude; Lachance, Sylvie; Cohen, Sandra; Delisle, Jean‐Sébastien; Kiss, Thomas; Sauvageau, Guy; Busque, Lambert; Ahmad, Imran; Bernard, Lea; Bambace, Nadia; Boumédine, Radia S.; Guertin, Marie‐Claude; et al.
Summary: Graft‐versus‐host disease (GVHD) is a major cause of transplant‐related mortality (TRM) after allogeneic haematopoietic stem cell transplantation (HSCT) and presents a challenge in haploidentical HSCT. GVHD may be prevented by ex vivo graft T‐cell depletion or in vivo depletion of proliferating lymphocytes. However, both approaches pose significant risks, particularly infections and relapse, compromising survival. A photodepletion strategy to eliminate alloreactive T cells from mismatched donor lymphocyte infusions (enabling administration without immunosuppression), was used to develop ATIR101, an adjunctive therapy for use after haploidentical HSCT. In this phase I dose‐finding study, 19 adults (median age: 54 years) with high‐risk haematological malignancies were treated with T‐cell‐depleted human leucocyte antigen‐haploidentical myeloablative HSCT followed by ATIR101 at doses of 1 × 10 4 –5 × 10 6  CD3 +  cells/kg (median 31 days post‐transplant). No patient received post‐transplant immunosuppression or developed grade III/IV acute GVHD, demonstrating the feasibility of ATIR101 infusion for evaluation in two subsequent phase 2 studies. Additionally, we report long‐term follow ‐up of patients treated with ATIR101 in this study. At 1 year, all 9 patients receiving doses of 0·3–2 × 10 6  CD3 +  cells/kg ATIR101 remained free of serious infections and after more than 8 years, TRM was 0%, relapse‐related mortality was 33% and overall survival was 67% in these patients.